Preparedness of health workers to face the risk of earthquake disasters in the Operating Room (OR) - Murdiyanto, Joko; Muhaji, Muhaji; Tri Wulandari, Endah (International Journal of Health Science and Technology, 2025)
According to Yogyakarta Province Regional Disaster Management Agency (BPBD) in the Indonesian Disaster Data and Information, ranking 1st among various disaster indices in the Yogyakarta Province. Health workers in all hospital units are important to prepare for earthquake disaster preparedness, one of which is health workers working in the operating room (OR). There has been no evaluation of preparedness in the operating room in the previous study, and as a form of preparedness evaluation in facing future earthquake disasters. The purpose of this study is to determine the preparedness of health workers to face the risk of earthquake disasters in the operating room (OR). The method employed a mixed-methods approach with a phased mixed approach, namely quantitative and qualitative in the research variables. The samples in this study consisted of all health workers in the PKU Muhammadiyah Yogyakarta General Hospital, totaling 20 people. The results of the study showed varying results on each indicator of healthcare workers' disaster preparedness in the operating room. There are several themes from the results of this study including: the concept of earthquakes, problems and solutions in operating rooms facing mass casualties, and earthquake preparedness in the operating room. This study describes knowledge about the daily habits of activities in the Central Surgical Installation (Operating Room) and illustrates the importance of a better understanding of regular phenomena so that it can be used as a basis for accurate estimates of how a hospital's operation room will face major disaster events and provide the required services.